Antibiotic spider silk: site-specific functionalisation of recombinant spider silk using ‘click’- chemistry - Harvey, D.; Bardelang, P.; Goodacre, S.L.; Cockayne, Alan; Thomas, Neil R. (Wiley, 2017)
The use of functionalised recombinant spider silk as a sustainable advanced biomaterial is currently an area of intense interest owing to spider silk’s intrinsic strength, toughness, biocompatibility and biodegradability. This paper demonstrates, for the first time, the site-specific chemical conjugation of different organic ligands that confer either antibiotic or fluorescent properties to spider silk. This has been achieved by the incorporation of the non-natural methionine analogue L-azidohomoalanine (L-Aha) using an E. coli methionine auxotroph and subsequent copper catalysed azide-alkyne cycloaddition (CuAAC) or ‘click chemistry’ functionalisation of 4RepCT3Aha. The 4RepCT3Aha protein can be modified either prior to, or post fibre formation increasing the versatility of this approach as demonstrated here by the formation of silk fibres bearing a defined ratio of two different fluorophores uniformly distributed along the fibres. Silk decorated with the fluoroquinone family broad spectrum antibiotic levofloxacin via a labile linker is shown to have significant antibiotic activity over a period of at least 5 days. The inherent low immunogenicity and pyrogenicity of spider silk should allow a diverse range of functionalised silks to be produced using these approaches that are tailored to applications including wound dressings and as tissue regeneration scaffolds.